Determinantes da taxa de difusão tecnológica na cogeração do setor sucroalcooleiro - NASCIMENTO, Fábio Nunes do (2010)
This study had as main objective to find the determinants of technology diffusion in the co-generation of energy in the sugar-alcohol sector. Specifically it was intended to work in order to analyze the relationship of technology diffusion in the process of polarization and regional growth; analyzing the composition of the Brazilian energy matrix and the share of energy generation from biomass of sugar cane; show the potential of power generation in the State of Goiás from co-generation and demonstrate that the change in technology used by sugar cane mills in Goiás can generate excess electricity for commercialization, besides the electricity supply for self-consumption. The methodology used for contemplation of the goals consisted of literature review and case study. The study allowed to reach the conclusion that the main determinants of technology diffusion in the sugar-alcohol sector are of economic order.